A 1D conical nanotubular TiO2/CdS heterostructure with superior photon-to-electron conversion - Zazpe, R; Sopha, H; Prikryl, J; Krbal, M; Mistrik, J; Dvorak, F; Hromadko, L; Macak, J M (Nanoscale, 2018)
Herein, a new strategy to efficiently harvest photons in solar cells is presented. A solar cell heterostructure is put forward, based on a 1D conical TiO2 nanotubular scaffold of high aspect ratio, homogenously coated with a thin few nm layer of CdS light absorber using atomic layer deposition (ALD). For the first time, a large variety of conical nanotube layers with a huge span of aspect ratios was utilized and ALD was used for the preparation of a uniform CdS coating within the entire high surface area of the TiO2 nanotubes. The resulting 1D conical CdS/TiO2 tubular heterostructure acts as a sink for photons. Due to the multiple light scattering and absorption events within this nanotubular sink, a large portion of photons (nearly 80%) is converted into electrons. It is the combination of the scaffold architecture and the light absorber present on the high surface area as a very thin layer, the optimized charge transport and multiple optical effects that make this heterostructure very promising for the next generation of highly performing solar cells.